Enterprise Ontology dalam Identifikasi Entitas Informasi: Studi Kasus Lembaga Penjaminan Mutu Pendidikan Kemendikbudristek - Isbandi, Isbandi (Jurnal Inspirasi, 2021)
ABSTRACT Information Entity as part of Information architecture is a form of information planning that can underlie the development of information models and the implementation of Information Technology in order to meet needs and improve business effectiveness. The meaning and role of information encourages the Education Quality Assurance Institute (LPMP) to build an information structure that can support the process of improving the quality of education at the primary and secondary levels. The process of extracting an understanding of the substance of the organization becomes an important pillar in identifying the entities and interactions of information needed in the development of an information model. The essence of the organization is obtained through the adoption of the Enterprise Ontology concept with the Design and Engineering Methodology for Organization (DEMO) methodology which is then used to design business architecture as the basis for identifying entity and transactional processes of information. The analysis and design produces information components and representations of information models that show the interactivity between organizational information entities. The results of the design using DEMO show that LPMP has 51 transactions with 49 information entities formed from 164 activities divided into 9 information management domains, and the information transactions obtained can be used as the basis for reviewing information received and sent across actors in the organization. ABSTRAK Entitas Informasi sebagai bagian Arsitektur informasi merupakan bentuk perencanaan informasi yang dapat melandasi pengembangan model informasi dan implementasi Teknologi Informasi dalam rangka memenuhi kebutuhan dan meningkatkan efektifitas bisnis. Arti dan peran informasi mendorong Lembaga Penjaminan Mutu Pendidikan (LPMP) untuk membangun struktur informasi yang dapat mendukung proses peningkatan mutu pendidikan jenjang pendidikan dasar dan menengah. Proses ekstraksi pemahaman tentang subtansi organisasi menjadi pilar penting dalam mengidentifikasi entitas dan interaksi informasi yang dibutuhkan dalam pengembangan model informasi. Esensi organisasi tersebut diperoleh melalui adopsi konsep Enterprise Ontology dengan metodologi Design and Engineering Methodology for Organization (DEMO) yang kemudian digunakan untuk merancang aristektur bisnis sebagai dasar identifikasi entitas dan proses transaksional informasi. Analisis dan perancangan menghasilkan komponen informasi dan representasi model informasi yang menunjukan interaktifitas antar entitas informasi organisasi. Hasil perancangan menggunakan DEMO menunjukan bahwa LPMP memiliki 51 transaksi dengan 49 entitas informasi yang terbentuk dari 164 aktivitas yang terbagi ke dalam 9 domain pengelolaan informasi, dan transaksi informasi yang diperoleh dapat dijadikan dasar peninjauan informasi yang diterima dan dikirimkan lintas aktor dalam organisasi.